Psychotherapy with somatosensory stimulation for endometriosis-associated pain: a randomized controlled trial - Meissner, Karin; Schweizer-Arau, Annemarie; Limmer, Anna; Preibisch, Christine; Popovici, Roxana; Lange, Isabel; de Oriol, Barbara; Beissner, Florian (Obstetrics & gynecology, 2016)
OBJECTIVE: - To evaluate whether psychotherapy with somatosensory stimulation is effective for the treatment of pain and quality of life in patients with endometriosis-related pain. - METHODS: - Patients with a history of endometriosis and chronic pelvic pain were randomized to either psychotherapy with somatosensory stimulation (ie, different techniques of acupuncture point stimulation) or wait-list control for 3 months, after which all patients were treated. The primary outcome was brain connectivity assessed by functional magnetic resonance imaging. Prespecified secondary outcomes included pain on 11-point numeric rating scales (maximal and average global pain, pelvic pain, dyschezia, and dyspareunia) and physical and mental quality of life. A sample size of 30 per group was planned to compare outcomes in the treatment group and the wait-list control group. - RESULTS: - From March 2010 through March 2012, 67 women (mean age 35.6 years) were randomly allocated to intervention (n=35) or wait-list control (n=32). In comparison with wait-list controls, treated patients showed improvements after 3 months in maximal global pain (mean group difference −2.1, 95% confidence interval [CI] −3.4 to −0.8; P=.002), average global pain (−2.5, 95% CI −3.5 to −1.4; P<.001), pelvic pain (−1.4, 95% CI −2.7 to −0.1; P=.036), dyschezia (−3.5, 95% CI −5.8 to −1.3; P=.003), physical quality of life (3.8, 95% CI 0.5-7.1, P=.026), and mental quality of life (5.9, 95% CI 0.6-11.3; P=.031); dyspareunia improved nonsignificantly (−1.8, 95% CI −4.4 to 0.7; P=.150). Improvements in the intervention group remained stable at 6 and 24 months, and control patients showed comparable symptom relief after delayed intervention. - CONCLUSION: - Psychotherapy with somatosensory stimulation reduced global pain, pelvic pain, and dyschezia and improved quality of life in patients with endometriosis. After 6 and 24 months, when all patients were treated, both groups showed stable improvements. - CLINICAL TRIAL REGISTRATION: - ClinicalTrials.gov, https://clinicaltrials.gov, NCT01321840.
Gesehen am 05.05.2020